2011
DOI: 10.1093/ndt/gfr545
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of neointimal hyperplasia by sirolimus-eluting expanded polytetrafluoroethylene (ePTFE) haemodialysis grafts in comparison with paclitaxel-coated grafts

Abstract: Neointimal hyperplasia was effectively suppressed by sirolimus-eluting grafts. However, the inhibitory effects of sirolimus-eluting grafts were weaker than those observed for paclitaxel-coated grafts in our previous study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…While it has been shown that ECs play a significant role in SMC regulation, few of the studies addressing endothelialization go one step further to also directly address intimal hyperplasia . Research to inhibit intimal hyperplasia directly in ePTFE grafts has mostly been limited to physical manufacturing alterations such as the addition of anastomotic cuffs, or delivery of antiproliferative drugs such as paclitaxel to inhibit SMC proliferation, but neither of these approaches specifically encourage endothelialization . Our group has previously demonstrated that FSP modification of ePTFE surfaces can be used to introduce EC‐selective ligands for cell attachment that simultaneously resist platelet deposition .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While it has been shown that ECs play a significant role in SMC regulation, few of the studies addressing endothelialization go one step further to also directly address intimal hyperplasia . Research to inhibit intimal hyperplasia directly in ePTFE grafts has mostly been limited to physical manufacturing alterations such as the addition of anastomotic cuffs, or delivery of antiproliferative drugs such as paclitaxel to inhibit SMC proliferation, but neither of these approaches specifically encourage endothelialization . Our group has previously demonstrated that FSP modification of ePTFE surfaces can be used to introduce EC‐selective ligands for cell attachment that simultaneously resist platelet deposition .…”
Section: Discussionmentioning
confidence: 99%
“…28 Research to inhibit intimal hyperplasia directly in ePTFE grafts has mostly been limited to physical manufacturing alterations such as the addition of anastomotic cuffs, or delivery of antiproliferative drugs such as paclitaxel to inhibit SMC proliferation, but neither of these approaches specifically encourage endothelialization. 16,29 Our group has previously demonstrated that FSP modification of ePTFE surfaces can be used to introduce EC-selective ligands for cell attachment that simultaneously resist platelet deposition. 17,18 In addition, we have shown that extracellular matrix-mimetic PEG-based hydrogels are a promising scaffold to modulate SMC proliferation, migration, and phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limus derivatives are a large family of compounds preventing either allograft rejections or restenosis after angioplasty. Conversely, systemic toxic effects, unspecific antiproliferation activity on ECs and SMCs, and variable efficacy associated with their usage in vitro or in vivo are at the basis of the reported controversial results [199][200][201][202][203].…”
Section: Cues For Thrombosis and Neointimal Hyperplasia Preventionmentioning
confidence: 99%
“…Sirolimus and Paclitaxel‐Eluting Grafts. A number of publications have documented that dip coating PTFE grafts with either paclitaxel (72) or sirolimus (73) (both antiproliferative agents) reduces neointimal hyperplasia and improves patency. Initial results suggest that the magnitude of neointimal hyperplasia reduction appears to be greater with paclitaxel than with sirolimus.…”
mentioning
confidence: 99%